2022-RA-1607-ESGO Optimal time interval between neoadjuvant platinum-based chemotherapy and interval debulking surgery. (20th October 2022) - Andrikopoulou, Angeliki; Apostolidou, Kleoniki; Theofanakis, Charalampos; Markellos, Christos; Skafida, Efthymia; Fiste, Oraianthi; Kaparelou, Maria; Koutsoukos, Konstantinos; Thomakos, Nikolaos; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Zagouri, Flora; et al.
Abstract : Introduction/Background: There is limited data on the optimal time interval between the last dose of neoadjuvant chemotherapy (NACT) and interval debulking surgery (IDS) in high-grade serous ovarian carcinoma (HGSC). Methodology: We retrospectively identified patients with stage IIIC/IV HGSC who had received NACT followed by IDS during a 15-year period (January 2003-December 2018) in the Oncology Department of Alexandra University Hospital that were further divided in two groups: the short (<4 weeks) and long (>4 weeks) interval groups. Results: Overall, 115 patients with HGSC stage IIIC/IV that underwent NACT and IDS were included in our analysis. Median age of diagnosis was 62.7 years (SD: 10.7; 39–86). Median PFS was 15.7 months (SD: 1.4; 95% CI: 12.9 – 18.4) and median OS was 44.65 (SD: 2.9; 95% CI: 38.8 – 50.5). Patients were categorized in groups according to interval from NACT to IDS (< 4 weeks (group A); 4 -5 weeks (group B); 5- 6 weeks (group C); >6 weeks (group D). Long time interval from IDS to NACT (> 4 weeks) correlated to poorer PFS ( p= 0.006) and OS ( p= 0.006). Median PFS was 26.6 months (95% CI: 24 – 29.2) for patients undergoing IDS < 4 weeks after NACT versus 14.4 months (95% CI: 12.6 – 16.2) for the > 4 weeks group ( p= 0.006). Median OS was 69.5 months (95% CI: 46.9 – 92.1) versus 38.7 months (95% CI: 31.1 – 46.2) respectively ( p= 0.006). On multivariate analysis, interval from NACT to IDS (< 4 weeks vs > 4 weeks) retained its statistical significance in terms of PFS ( p= 0.004) and OS ( p= 0.002) along with optimal debulking, performance status and administration of bevacizumab (all p< 0.05). Conclusion: We have demonstrated that performing IDS within four weeks after NACT may be associated with better survival outcomes.